Using Template Matching to Detect Hidden Fluid Release Episodes Beneath Crater Lakes in Ruapehu, Copahue, and Kawah Ijen Volcanoes - Ardid, A. (2023)
Volcano crater lakes, while picturesque, can sometimes mask the occurrence of small eruptions or hydrothermal fluid release events. However, these seemingly hidden events hold a wealth of valuable information about the underlying volcanic conduit and may pose risks to those near the volcano’s summit. This study presents a novel method for identifying these hard-to-detect fluid release events by examining seismic data from Ruapehu volcano in New Zealand. We undertake a multi-timescale template-matching analysis that uses a newly discovered seismic eruption precursor, to identify patterns related to the rapid consolidation of hydrothermal seals, pressurization processes, and the subsequent release of hydrothermal fluids. As a result, we identified a potential instance of sudden fluid-release events that were previously unnoticed due to the presence of the crater lake. Our findings support a conceptual model of cyclic pressure variation within the conduit beneath an active crater lake. This model involves the formation and disruption of seals, followed by depressurization through hydrothermal fluid release events. Fluid discharge recession recorded as seismic amplitude decay, provides information about the properties of the reservoir, conduit, and the fluid being discharged. We also applied this technique to Kawah-Ijen (Indonesia) and Copahue (Chile-Argentina), identifying multiple potential events at these volcanoes. These findings enhance our understanding of the conditions leading to explosive eruptions, including those that could breach the crater lake.